Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2000
DOI: 10.1115/2000-gt-0284
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Influence of Rotor Blades on Hot Gas Ingestion Into the Upstream Cavity of an Axial Turbine Stage

Abstract: The phenomenon of hot gas ingestion through turbine rim seals is experimentally and numerically investigated for a complete stage with nozzle guide vanes and uncooled helicopter turbine rotor blades. In the experimental part, two different geometrical rim seal configurations are examined: 1. a simple axial gap between rotor and stator disk and 2. an axial gap between the rotor disk and a rim seal lip at the periphery of the stator disk. The results obtained are compared to experiments carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Chew et al reported both experimental and 3D computational fluid dynamics (CFD) results and concluded that inertial effects associated with the swirl component of velocity had an important influence on the flow. The combined influence of pressure asymmetries due to stationary vanes and rotating blades was noted by Green and Turner [8] and Bohn et al [9] who measured ingestion with both vanes and blades present. Bohn et al also presented unsteady CFD solutions showing some qualitative agreement with their data.…”
Section: Introductionmentioning
confidence: 81%
“…Chew et al reported both experimental and 3D computational fluid dynamics (CFD) results and concluded that inertial effects associated with the swirl component of velocity had an important influence on the flow. The combined influence of pressure asymmetries due to stationary vanes and rotating blades was noted by Green and Turner [8] and Bohn et al [9] who measured ingestion with both vanes and blades present. Bohn et al also presented unsteady CFD solutions showing some qualitative agreement with their data.…”
Section: Introductionmentioning
confidence: 81%
“…At engine conditions density differences are likely to be significant, so momentum or mass flux ratios may eventually prove more useful in correlating results. Some experiments including both rotor and stator blade rows have been reported by Green and Turner (1992) and Bohn et al (2000). Both sets of workers found evidence that the presence of rotor blades could improve sealing effectiveness, but Bohn et al found the opposite trend for a different seal design, and their blades had a surprisingly large effect on the pressure asymmetry due to the vanes.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al (2000) have also shown some agreement between steady CFD solutions and measurement from pressure tappings for a rim sealing rig including vanes and rotating blades. In another very recent paper Bohn et al (2000) included 3D, unsteady CFD calculations including both vanes and blades. They showed some differences in the calculated and measured levels of ingestion but obtained some qualitative agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al 17 showed the blades to have a positive effect in reducing ingestion. By contrast, Bohn et al 18 found the opposite effect, which was attributed to the increase of average static pressure asymmetry in the annulus due to the presence of the blades. The latter is more consistent with the findings of the present work.…”
Section: Introductionmentioning
confidence: 91%